A new performance evaluation scheme for jet engine vibration signal denoising. (August 2016) - Sadooghi, Mohammad Saleh; Esmaeilzadeh Khadem, Siamak
Abstract: Denoising of a cargo-plane jet engine compressor vibration signal is investigated in this article. Discrete wavelet transform and two families of Donoho–Johnston and parameter method thresholding, are applied to vibration signal. Eighty four combinations of wavelet thresholding and mother wavelet are evaluated. A new performance evaluation scheme for optimal selection of mother wavelet and thresholding method combination is proposed in this paper, which is make a trade off between four performance criteria of signal to noise ratio, percentage root mean square difference, Cross-correlation, and mean square error. Dmeyer mother wavelet (dmey) combined with Rigorous SURE thresholding has the maximum trade off value and was selected as the most appropriate combination for denoising of the signal. It was shown that inappropriate combination leads to data losing. Also higher performance of proposed trade off with respect to other criteria was proven graphically. Highlights: A jet engine vibration signal is denoised by an optimal new scheme. A new performance evaluation scheme for optimal selection of mother wavelet and thresholding method combination is proposed. Eighty four combinations of wavelet thresholding and mother wavelet are evaluated. Dmeyer mother wavelet combined with Rigorous SURE thresholding is introduced as the best combination. Inappropriate combination leads to data losing.